Variability Effect of Witchweed [Striga hermonthica(Del.) Benth.]Populations on the Performance of [Sorghum bicolor) cv. ‘Abu sabeen’ in Sudan - Dafaallah, Awadallah B; Babiker, Abd Elgabar T; Zain El Abdeen, Mohammed H. (University of Khartoum Journal of Agricultural Sciences, 2023)
<span dir="ltr" style="left: calc(var(--scale-factor)*185.33px); top: calc(var(--scale-factor)*313.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.973933);" role="presentation">Field <span dir="ltr" style="left: calc(var(--scale-factor)*215.45px); top: calc(var(--scale-factor)*313.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.927299);" role="presentation">surveys and a green house experiment were conducted <span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*326.95px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.945093);" role="presentation">during season 2009/2010 to investigate variability and host specificity of <span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*340.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.925384);" role="presentation">witchweed <span dir="ltr" style="left: calc(var(--scale-factor)*189.89px); top: calc(var(--scale-factor)*340.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.937715);" role="presentation">Striga <span dir="ltr" style="left: calc(var(--scale-factor)*227.67px); top: calc(var(--scale-factor)*340.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.917722);" role="presentation">hermonthica <span dir="ltr" style="left: calc(var(--scale-factor)*296.71px); top: calc(var(--scale-factor)*340.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.912104);" role="presentation">populations. <span dir="ltr" style="left: calc(var(--scale-factor)*364.15px); top: calc(var(--scale-factor)*340.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.896372);" role="presentation">The <span dir="ltr" style="left: calc(var(--scale-factor)*391.02px); top: calc(var(--scale-factor)*340.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.998274);" role="presentation">field <span dir="ltr" style="left: calc(var(--scale-factor)*421.38px); top: calc(var(--scale-factor)*340.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.881858);" role="presentation">surveys <span dir="ltr" style="left: calc(var(--scale-factor)*466.23px); top: calc(var(--scale-factor)*340.75px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.897809);" role="presentation">were <span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*354.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.889323);" role="presentation">conducted <span dir="ltr" style="left: calc(var(--scale-factor)*186.37px); top: calc(var(--scale-factor)*354.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.999572);" role="presentation">in <span dir="ltr" style="left: calc(var(--scale-factor)*203.33px); top: calc(var(--scale-factor)*354.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.794351);" role="presentation">S. <span dir="ltr" style="left: calc(var(--scale-factor)*219.88px); top: calc(var(--scale-factor)*354.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.920994);" role="presentation">hermonthica <span dir="ltr" style="left: calc(var(--scale-factor)*288.29px); top: calc(var(--scale-factor)*354.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.895171);" role="presentation">endemic <span dir="ltr" style="left: calc(var(--scale-factor)*336.39px); top: calc(var(--scale-factor)*354.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.818927);" role="presentation">areas <span dir="ltr" style="left: calc(var(--scale-factor)*368.52px); top: calc(var(--scale-factor)*354.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.0137);" role="presentation">in <span dir="ltr" style="left: calc(var(--scale-factor)*385.54px); top: calc(var(--scale-factor)*354.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.92524);" role="presentation">Gadarif, <span dir="ltr" style="left: calc(var(--scale-factor)*432.67px); top: calc(var(--scale-factor)*354.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.908715);" role="presentation">Gezira <span dir="ltr" style="left: calc(var(--scale-factor)*472.40px); top: calc(var(--scale-factor)*354.55px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.863568);" role="presentation">and <span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*368.35px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.913305);" role="presentation">Kordofan to collect seeds from striga plants growing under their respective <span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*382.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.8655);" role="presentation">hosts. A <span dir="ltr" style="left: calc(var(--scale-factor)*180.61px); top: calc(var(--scale-factor)*382.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.940626);" role="presentation">total <span dir="ltr" style="left: calc(var(--scale-factor)*209.26px); top: calc(var(--scale-factor)*382.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.9996);" role="presentation">of <span dir="ltr" style="left: calc(var(--scale-factor)*226.53px); top: calc(var(--scale-factor)*382.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.955005);" role="presentation">fifteen S. <span dir="ltr" style="left: calc(var(--scale-factor)*281.45px); top: calc(var(--scale-factor)*382.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.917722);" role="presentation">hermonthica <span dir="ltr" style="left: calc(var(--scale-factor)*349.39px); top: calc(var(--scale-factor)*382.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.912712);" role="presentation">populations <span dir="ltr" style="left: calc(var(--scale-factor)*412.74px); top: calc(var(--scale-factor)*382.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.893656);" role="presentation">were <span dir="ltr" style="left: calc(var(--scale-factor)*443.21px); top: calc(var(--scale-factor)*382.15px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.913496);" role="presentation">collected. <span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*395.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.961285);" role="presentation">Twelve S. <span dir="ltr" style="left: calc(var(--scale-factor)*183.65px); top: calc(var(--scale-factor)*395.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.917722);" role="presentation">hermonthica <span dir="ltr" style="left: calc(var(--scale-factor)*248.81px); top: calc(var(--scale-factor)*395.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.93967);" role="presentation">populations, were collected from under sorghum <span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*409.77px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.946748);" role="presentation">and three. were collected from under millet. <span dir="ltr" style="left: calc(var(--scale-factor)*351.79px); top: calc(var(--scale-factor)*409.77px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.915148);" role="presentation">Laboratory and green house <span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*423.57px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.89821);" role="presentation">experiments <span dir="ltr" style="left: calc(var(--scale-factor)*195.89px); top: calc(var(--scale-factor)*423.57px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.893656);" role="presentation">were <span dir="ltr" style="left: calc(var(--scale-factor)*226.61px); top: calc(var(--scale-factor)*423.57px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.887504);" role="presentation">undertaken <span dir="ltr" style="left: calc(var(--scale-factor)*287.43px); top: calc(var(--scale-factor)*423.57px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.8616);" role="presentation">at <span dir="ltr" style="left: calc(var(--scale-factor)*303.61px); top: calc(var(--scale-factor)*423.57px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.879664);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*325.80px); top: calc(var(--scale-factor)*423.57px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.94524);" role="presentation">horticulture <span dir="ltr" style="left: calc(var(--scale-factor)*389.37px); top: calc(var(--scale-factor)*423.57px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.918163);" role="presentation">nursery, <span dir="ltr" style="left: calc(var(--scale-factor)*435.89px); top: calc(var(--scale-factor)*423.57px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.93654);" role="presentation">Faculty <span dir="ltr" style="left: calc(var(--scale-factor)*479.41px); top: calc(var(--scale-factor)*423.57px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.9996);" role="presentation">of <span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*437.37px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.982509);" role="presentation">Agricultural Sciences, University of Gezira, Sudan, to test the viability <span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*451.17px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.96962);" role="presentation">and infectivity of seeds of witchweed populations <span dir="ltr" style="left: calc(var(--scale-factor)*385.75px); top: calc(var(--scale-factor)*451.17px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.960711);" role="presentation">on sorghum, cultivar <span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*464.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.02384);" role="presentation">“Abu-<span dir="ltr" style="left: calc(var(--scale-factor)*159.50px); top: calc(var(--scale-factor)*464.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.875571);" role="presentation">sabeen”, a <span dir="ltr" style="left: calc(var(--scale-factor)*226.00px); top: calc(var(--scale-factor)*464.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.982967);" role="presentation">highly <span dir="ltr" style="left: calc(var(--scale-factor)*266.76px); top: calc(var(--scale-factor)*464.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.889703);" role="presentation">susceptible <span dir="ltr" style="left: calc(var(--scale-factor)*330.31px); top: calc(var(--scale-factor)*464.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.973396);" role="presentation">cultivar. <span dir="ltr" style="left: calc(var(--scale-factor)*380.07px); top: calc(var(--scale-factor)*464.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.891239);" role="presentation">Data <span dir="ltr" style="left: calc(var(--scale-factor)*412.82px); top: calc(var(--scale-factor)*464.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.912608);" role="presentation">collected <span dir="ltr" style="left: calc(var(--scale-factor)*466.30px); top: calc(var(--scale-factor)*464.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.896425);" role="presentation">were <span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*478.77px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.893307);" role="presentation">transformed as necessary and <span dir="ltr" style="left: calc(var(--scale-factor)*278.09px); top: calc(var(--scale-factor)*478.77px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.941729);" role="presentation">were statistically <span dir="ltr" style="left: calc(var(--scale-factor)*364.39px); top: calc(var(--scale-factor)*478.77px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.871637);" role="presentation">analysed. <span dir="ltr" style="left: calc(var(--scale-factor)*413.38px); top: calc(var(--scale-factor)*478.77px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.900461);" role="presentation">Results showed <span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*492.57px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.9);" role="presentation">that a<span dir="ltr" style="left: calc(var(--scale-factor)*158.18px); top: calc(var(--scale-factor)*492.57px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.25393);" role="presentation">ll <span dir="ltr" style="left: calc(var(--scale-factor)*170.18px); top: calc(var(--scale-factor)*492.57px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.927814);" role="presentation">S. hermonthica <span dir="ltr" style="left: calc(var(--scale-factor)*250.49px); top: calc(var(--scale-factor)*492.57px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.944895);" role="presentation">seed populations displayed high germination % <span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*506.37px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.88913);" role="presentation">rang<span dir="ltr" style="left: calc(var(--scale-factor)*150.86px); top: calc(var(--scale-factor)*506.37px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.957901);" role="presentation">ing <span dir="ltr" style="left: calc(var(--scale-factor)*170.66px); top: calc(var(--scale-factor)*506.37px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.975);" role="presentation">from <span dir="ltr" style="left: calc(var(--scale-factor)*198.65px); top: calc(var(--scale-factor)*506.37px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.899743);" role="presentation">87.0 % <span dir="ltr" style="left: calc(var(--scale-factor)*238.73px); top: calc(var(--scale-factor)*506.37px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.936);" role="presentation">to <span dir="ltr" style="left: calc(var(--scale-factor)*252.65px); top: calc(var(--scale-factor)*506.37px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.899743);" role="presentation">92.3 %<span dir="ltr" style="left: calc(var(--scale-factor)*288.17px); top: calc(var(--scale-factor)*506.37px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.934653);" role="presentation">, regardless of the <span dir="ltr" style="left: calc(var(--scale-factor)*382.51px); top: calc(var(--scale-factor)*506.37px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.837893);" role="presentation">area, <span dir="ltr" style="left: calc(var(--scale-factor)*409.99px); top: calc(var(--scale-factor)*506.37px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.934549);" role="presentation">location and <span dir="ltr" style="left: calc(var(--scale-factor)*475.06px); top: calc(var(--scale-factor)*506.37px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.879664);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*520.17px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.902449);" role="presentation">host crop. C<span dir="ltr" style="left: calc(var(--scale-factor)*191.69px); top: calc(var(--scale-factor)*520.17px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.907571);" role="presentation">apsules per plant, shoot dry weight and underground plantlets <span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*533.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.938353);" role="presentation">of emergent striga <span dir="ltr" style="left: calc(var(--scale-factor)*225.17px); top: calc(var(--scale-factor)*533.97px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.958026);" role="presentation">were highest on the respective host. It is noteworthy <span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*547.80px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.9564);" role="presentation">that some of the millet s<span dir="ltr" style="left: calc(var(--scale-factor)*250.73px); top: calc(var(--scale-factor)*547.80px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.937789);" role="presentation">triga <span dir="ltr" style="left: calc(var(--scale-factor)*276.65px); top: calc(var(--scale-factor)*547.80px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.912712);" role="presentation">populations <span dir="ltr" style="left: calc(var(--scale-factor)*336.79px); top: calc(var(--scale-factor)*547.80px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.949312);" role="presentation">displayed limited <span dir="ltr" style="left: calc(var(--scale-factor)*425.14px); top: calc(var(--scale-factor)*547.80px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.864112);" role="presentation">emergence <span dir="ltr" style="left: calc(var(--scale-factor)*481.06px); top: calc(var(--scale-factor)*547.80px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.8616);" role="presentation">at <span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*561.60px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.89955);" role="presentation">60 <span dir="ltr" style="left: calc(var(--scale-factor)*149.53px); top: calc(var(--scale-factor)*561.60px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.860931);" role="presentation">days <span dir="ltr" style="left: calc(var(--scale-factor)*179.33px); top: calc(var(--scale-factor)*561.60px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.916);" role="presentation">after <span dir="ltr" style="left: calc(var(--scale-factor)*209.19px); top: calc(var(--scale-factor)*561.60px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.916195);" role="presentation">crop <span dir="ltr" style="left: calc(var(--scale-factor)*238.44px); top: calc(var(--scale-factor)*561.60px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.866111);" role="presentation">emergence <span dir="ltr" style="left: calc(var(--scale-factor)*298.39px); top: calc(var(--scale-factor)*561.60px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.89955);" role="presentation">on <span dir="ltr" style="left: calc(var(--scale-factor)*318.30px); top: calc(var(--scale-factor)*561.60px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.898972);" role="presentation">sorghum <span dir="ltr" style="left: calc(var(--scale-factor)*368.19px); top: calc(var(--scale-factor)*561.60px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.863568);" role="presentation">and <span dir="ltr" style="left: calc(var(--scale-factor)*393.38px); top: calc(var(--scale-factor)*561.60px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.890044);" role="presentation">produced <span dir="ltr" style="left: calc(var(--scale-factor)*445.90px); top: calc(var(--scale-factor)*561.60px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.860655);" role="presentation">capsules. <span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*575.40px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.9412);" role="presentation">S. hermonthica <span dir="ltr" style="left: calc(var(--scale-factor)*211.97px); top: calc(var(--scale-factor)*575.40px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.00063);" role="presentation">populations significantly reduced growth and yield of <span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*589.20px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.896941);" role="presentation">sorghum. <span dir="ltr" style="left: calc(var(--scale-factor)*182.17px); top: calc(var(--scale-factor)*589.20px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.938692);" role="presentation">However, <span dir="ltr" style="left: calc(var(--scale-factor)*236.74px); top: calc(var(--scale-factor)*589.20px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.879664);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*259.16px); top: calc(var(--scale-factor)*589.20px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.902463);" role="presentation">magnitude <span dir="ltr" style="left: calc(var(--scale-factor)*317.34px); top: calc(var(--scale-factor)*589.20px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.9996);" role="presentation">of <span dir="ltr" style="left: calc(var(--scale-factor)*334.96px); top: calc(var(--scale-factor)*589.20px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.879664);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*357.27px); top: calc(var(--scale-factor)*589.20px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.862284);" role="presentation">damage <span dir="ltr" style="left: calc(var(--scale-factor)*402.25px); top: calc(var(--scale-factor)*589.20px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.888754);" role="presentation">attained <span dir="ltr" style="left: calc(var(--scale-factor)*447.82px); top: calc(var(--scale-factor)*589.20px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.955643);" role="presentation">by <span dir="ltr" style="left: calc(var(--scale-factor)*467.48px); top: calc(var(--scale-factor)*589.20px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.839677);" role="presentation">each <span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*603.00px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.927312);" role="presentation">population <span dir="ltr" style="left: calc(var(--scale-factor)*189.25px); top: calc(var(--scale-factor)*603.00px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.87104);" role="presentation">was <span dir="ltr" style="left: calc(var(--scale-factor)*216.12px); top: calc(var(--scale-factor)*603.00px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.892554);" role="presentation">highest <span dir="ltr" style="left: calc(var(--scale-factor)*259.05px); top: calc(var(--scale-factor)*603.00px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.89955);" role="presentation">on <span dir="ltr" style="left: calc(var(--scale-factor)*279.32px); top: calc(var(--scale-factor)*603.00px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.879664);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*302.23px); top: calc(var(--scale-factor)*603.00px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.887271);" role="presentation">respective <span dir="ltr" style="left: calc(var(--scale-factor)*358.96px); top: calc(var(--scale-factor)*603.00px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.887164);" role="presentation">host, <span dir="ltr" style="left: calc(var(--scale-factor)*390.54px); top: calc(var(--scale-factor)*603.00px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.8824);" role="presentation">thus <span dir="ltr" style="left: calc(var(--scale-factor)*418.90px); top: calc(var(--scale-factor)*603.00px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.93512);" role="presentation">indica<span dir="ltr" style="left: calc(var(--scale-factor)*448.18px); top: calc(var(--scale-factor)*603.00px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.967322);" role="presentation">ting <span dir="ltr" style="left: calc(var(--scale-factor)*475.06px); top: calc(var(--scale-factor)*603.00px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.879664);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*616.80px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.953727);" role="presentation">existence of inter-<span dir="ltr" style="left: calc(var(--scale-factor)*220.13px); top: calc(var(--scale-factor)*616.80px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.935562);" role="presentation">crop specialization <span dir="ltr" style="left: calc(var(--scale-factor)*317.47px); top: calc(var(--scale-factor)*616.80px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.938754);" role="presentation">and probably t<span dir="ltr" style="left: calc(var(--scale-factor)*390.67px); top: calc(var(--scale-factor)*616.80px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.962174);" role="presentation">he existence of two <span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*630.60px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.922622);" role="presentation">strains of <span dir="ltr" style="left: calc(var(--scale-factor)*178.13px); top: calc(var(--scale-factor)*630.60px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.906991);" role="presentation">S. hermonthica<span dir="ltr" style="left: calc(var(--scale-factor)*251.45px); top: calc(var(--scale-factor)*630.60px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.932566);" role="presentation">, one specific to sorghum and the other to millet. <span dir="ltr" style="left: calc(var(--scale-factor)*129.62px); top: calc(var(--scale-factor)*644.40px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.914842);" role="presentation">These findings <span dir="ltr" style="left: calc(var(--scale-factor)*204.65px); top: calc(var(--scale-factor)*644.40px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.920512);" role="presentation">may <span dir="ltr" style="left: calc(var(--scale-factor)*228.77px); top: calc(var(--scale-factor)*644.40px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.936213);" role="presentation">provide <span dir="ltr" style="left: calc(var(--scale-factor)*269.21px); top: calc(var(--scale-factor)*644.40px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.906134);" role="presentation">clues <span dir="ltr" style="left: calc(var(--scale-factor)*297.43px); top: calc(var(--scale-factor)*644.40px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.89955);" role="presentation">on <span dir="ltr" style="left: calc(var(--scale-factor)*313.03px); top: calc(var(--scale-factor)*644.40px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.949095);" role="presentation">the complexity of <span dir="ltr" style="left: calc(var(--scale-factor)*402.07px); top: calc(var(--scale-factor)*644.40px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.901606);" role="presentation">breeding <span dir="ltr" style="left: calc(var(--scale-factor)*447.70px); top: calc(var(--scale-factor)*644.40px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.898972);" role="presentation">sorghum